Surveillance and System Avoidance - Brayne, Sarah (American Sociological Review, 2014)
The degree and scope of criminal justice surveillance increased dramatically in the United States over the past four decades. Recent qualitative research suggests the rise in surveillance may be met with a concomitant increase in efforts to evade it. To date, however, there has been no quantitative empirical test of this theory. In this article, I introduce the concept of “system avoidance,” whereby individuals who have had contact with the criminal justice system avoid surveilling institutions that keep formal records. Using data from Add Health ( n = 15,170) and the NLSY97 ( n = 8,894), I find that individuals who have been stopped by police, arrested, convicted, or incarcerated are less likely to interact with surveilling institutions, including medical, financial, labor market, and educational institutions, than their counterparts who have not had criminal justice contact. By contrast, individuals with criminal justice contact are no less likely to participate in civic or religious institutions. Because criminal justice contact is disproportionately distributed, this study suggests system avoidance is a potential mechanism through which the criminal justice system contributes to social stratification: it severs an already marginalized subpopulation from institutions that are pivotal to desistance from crime and their own integration into broader society.